Risk-Informed Information Practice: Ways of Knowing in an Uncertain World - Hicks, Alison (Global Perspectives on Library and Information Science, 2025)
How do people become informed about risk and why is this important? This book draws upon three case studies to interrogate risk’s informational thread, including how people map and orient themselves to risk information as well as how these activities shape their increasingly knowledgeable performance within a risk situation. This book offers a novel theoretical, methodological and practical approach for considering how risk responses are informed. As the first full-length treatment of this topic, the book provides insight into how people become knowledgeable about risk, including the various sources of information on which they draw and the social and political conditions that shape access to these information environments. In further centring developmental change, the book also sheds light onto the discontinuities that risk creates as well as the need to adjust to alterations in roles and responsibilities. Resulting in the production of a robust definition and conceptual framework for risk-informed information practice, the book’s broad approach, which involves a consideration of risk understanding alongside the more typical risk perception and management, further integrates reflection on the methodological implications of this work. The book’s focus on research and practice means that it will be of interest to risk and information professionals, including those with responsibility for risk messaging, information literacy instruction and patient interaction. The conceptual focus further means that this book will be invaluable for information literacy and risk scholars looking to extend their understanding of how people develop knowing when things of value are at stake.